Border crossing : Russian literature into film - Burry, Alexander; White, Frederick H., 1970- (Edinburgh University Press, 2016)
Examines the ways in which Russian texts are altered in order to suit new cinematic environments. Each time a border is crossed there are cultural, political and social issues to be considered. Applying the metaphor of the 'border crossing' from one temporal or spatial territory into another, Border Crossing: Russian Literature into Film examines the way classic Russian texts have been altered to suit new cinematic environments. In these essays, international scholars examine how political and economic circumstances, from a shifting Soviet political landscape to the perceived demands of American and European markets, have played a crucial role in dictating how filmmakers transpose their cinematic hypertext into a new environment. Rather than focus on the degree of accuracy or fidelity with which these films address their originating texts, this innovative collection explores the role of ideological, political and other cultural pressures that can affect the transformation of literary narratives into cinematic offerings. Contributors. Otto Boele is an Associate Professor of Russian literature at the University of Leiden Alexander Burry is an Associate Professor of Slavic and East European Languages and Cultures at The Ohio State University Olga Peters Hasty is a Professor in the Department of Slavic Languages and Literatures at Princeton University Dennis Ioffe is an Assistant Professor in the Department of Languages and Cultures at Ghent University Thomas Leitch teaches English and directs the Film Studies program at the University of Delaware Yuri Leving is Professor of Russian Literature and Film in the Department of Russian Studies, Dalhousie University, Canada Ronald Meyer teaches the seminar in Russian literary translation at Columbia University Robert Mulcahy is a Lecturer in Slavic at The Ohio State University S. Ceilidh Orr is Lecturer at The Ohio State University Alastair Renfrew is Reader in English and Comparative Literature at Durham University Frederick H. White is Associate Vice President, Academic Affairs, Engaged Learning at Utah Valley University